Activities at a mathematics fair: Possibilities for an educational praxis - Zabel, Marília [UNESP]; Dos Santos Malheiros, Ana Paula [UNESP] (My University, 2023)
This article is the result of an investigation that aimed to characterize the mathematical activities developed in the classroom and presented at the Regional Mathematics Fair of Rio do Sul (SC), to support an educational praxis. Considering the research qualitative approach, our material included the reports of experiences of four works presented at that fair and interviews with one of the exhibiting students of each of the works. The analysis of those materials was anchored in Paulo Freire's legacy, especially the notions of praxis and dialogue. In this process, we obtained four categories: 1) choice of the topic to be studied; 2) mathematization; 3) dialogue, collaboration, and involvement with the school community, and 4) action-reflection-Transformation. By interpreting the categories, we envisioned the possibility of an educational praxis in which students and educators make an initial world reading in the context of perception, develop mathematical knowledge to understand this reading, and aim for a collective transformative action. Furthermore, we reinforce the importance of events such as the mathematics fair for the promotion and dissemination of these activities.
Atividades na Feira de Matemática: possibilidades para uma práxis educative